Ethical evaluation of capital punishment in cultural perspective the Islamic case of apostasy - Açıkgenç, Ali Abdullah (My University, 2019)
Capital punishment has begun to be dealt with in ethics as a general moral problem. In this study, we will try to make a philosophical, moral and legal evaluation in order to deal with the morality of this punishment from a cultural point of view. As it is known, we face two important concepts in capital punishment: life and death. These two phenomena should be examined in relation to the death penalty. For this reason, the nature and meaning of life and death will be analyzed philosophically and the morality of a punishment in the sense of ending life will be analyzed. If a problem is moral, the two most important moral concepts are undoubtedly the concepts of good and evil. The death penalty will be examined in terms of these concepts and the philosophers, especially Kant and Hegel, who give important opinions on this subject will be discussed in detail. The views of Cesare Beccaria, who for the first time philosophically advocated the abolition of the death penalty and proposed a legal system based on it, will be examined in this context. The thesis will be concluded by examining a sample case of Islamic law that deals with the subject from a cultural perspective. Our case is apostasy which is interpreted that as not a creedal crime but a danger that threatens the state and society. In Islamic law, it is not possible to abolish capital punishment as the Qur'an imposes the death penalty for premeditated murder. Although the Qur'an imposed this punishment to only one crime, it still advises to forgive. So it can be said that in this case, even if the death penalty is not abolished it is restricted by Islamic law. As a result, it would be appropriate to state that it is very difficult to solve this problem both legally and morally.

Ölüm cezası genel ahlak sorunu olarak etik içerisinde ele alınmaya başlamıştır. Bu cezanın ahlakiliğini kültürel açıdan ele alan bu çalışmamızda felsefi, ahlaki ve hukuki değerlendirme yapmaya çalışılacaktır. Bilindiği gibi ölüm cezasında iki önemli kavramla karşılaşmaktayız: hayat ve ölüm. Bu iki olgunun ölüm cezasına olan ilgisi açısından incelenmesi gerekir. Onun için hayatın ve ölümün mahiyeti ve anlamı felsefi olarak incelenerek hayatın sonlandırılması anlamında olan bir cezanın ahlakiliği tahlil edilecektir. Bir sorun ahlaki ise ahlaken en önemli incelenen iki kavram şüphesiz ki iyi ve kötü kavramlarıdır. Ölüm cezası bu kavramlar açısından incelenecek ve bu konuda önemli görüş belirten filozoflar, özellikle Kant ve Hegel ayrıntılı olarak tartışılacaktır. Ölüm cezasının kaldırılmasını ilk defa ahlaki gerekçelerle felsefi olarak savunan ve buna dayalı hukuk sistemi öneren Cesare Beccaria’nın görüşleri bu bağlamda incelenecektir. Tez, konuyu kültürel açıdan ele alan İslam hukukundan bir örneğin incelenmesi ile sonuca kavuşturulacaktır. Örnek konumuz ise irtidat suçuna verilen ölüm cezasıdır. Bu konu incelendiğinde irtidatın, itikadi bir suç olmadığını aksine devlet ve toplumu tehdit eden bir durum olarak yorumlanmıştır. Kültürel açıdan İslam ele alındığında Kur’an’da ölüm cezasının olmasından dolayı tamamen kaldırılmasının mümkün olmadığı görülmektedir. Ancak Kur’an’da ölüm cezası verilen sadece bir suç (amden katil için) olduğu halde buna dahi tavsiyesi affetmektir. O halde bu durumda denebilir ki, ölüm cezası kaldırılmasa dahi sınırlandırılmıştır. Sonuçta hukuki ve ahlaki açıdan bu sorunun çözümlenmesinin çok zor olduğunu belirtmek yerinde olur.
Tez (Yüksek Lisans) - Yıldız Teknik Üniversitesi, Sosyal Bilimler Enstitüsü, 2019
Keywords: Capital punishment; Value of life; Biological perspective in death penalty; Apostasy; Ölüm cezası; Hayatın değeri; Ölüm cezasına biyolojik yaklaşım; İrtidat